Endometrial Glucose Transporters in Health and Disease - Vrhovac Madunić, Ivana; Karin-Kujundžić, Valentina; Madunić, Josip; Šola, Ida Marija; Šerman, Ljiljana (Frontiers in Cell and Developmental Biology, 2021)
Pregnancy loss is a frequent occurrence during the peri-implantation period, when there is high glucose demand for embryonic development and endometrial decidualization. Glucose is among the most essential uterine fluid components required for those processes. Numerous studies associate abnormal glucose metabolism in the endometrium with a higher risk of adverse pregnancy outcomes. The endometrium is incapable of synthesizing glucose, which thus must be delivered into the uterine lumen by glucose transporters (GLUTs) and/or the sodium-dependent glucose transporter 1 (SGLT1). Among the 26 glucose transporters (14 GLUTs and 12 SGLTs) described, 10 (9 GLUTs and SGLT1) are expressed in rodents and 8 (7 GLUTs and SGLT1) in the human uterus. This review summarizes present knowledge on the most studied glucose transporters in the uterine endometrium (GLUT1, GLUT3, GLUT4, and GLUT8), whose data regarding function and regulation are still lacking. We present the recently discovered SGLT1 in the mouse and human endometrium, responsible for controlling glycogen accumulation essential for embryo implantation. Moreover, we describe the epigenetic regulation of endometrial GLUTs, as well as signaling pathways included in uterine GLUT’s expression. Further investigation of the GLUTs function in different endometrial cells is of high importance, as numerous glucose transporters are associated with infertility, polycystic ovary syndrome, and gestational diabetes.